2003
DOI: 10.4218/etrij.03.0102.0002
|View full text |Cite
|
Sign up to set email alerts
|

A High-Gain Microstrip Patch Array Antenna Using a Superstrate Layer

Abstract: A dielectric superstrate layer above a microstrip patch antenna has remarkable effects on its gain and resonant characteristics. This paper experimentally investigates the effect of a superstrate layer for high gain on microstrip patch antennas. We measured the gain of antennas with and without a superstrate and found that the gain of a single patch with a superstrate was enhanced by about 4 dBi over the one without a superstrate at 12 GHz. The impedance bandwidths of a single patch with and without a superstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…High-gain microstrip array using a superstrate layer and a feed network is proposed [30] but it suffers from large size and high SLL. Three-dimensional efficient directive antenna arrays are proposed in [31].…”
Section: Introductionmentioning
confidence: 99%
“…High-gain microstrip array using a superstrate layer and a feed network is proposed [30] but it suffers from large size and high SLL. Three-dimensional efficient directive antenna arrays are proposed in [31].…”
Section: Introductionmentioning
confidence: 99%
“…It is well know that high directive antennas play an important role in many practical applications. Many conventional efforts have been made to improve the antenna directivity such as parasitic patches, array of patch antennas, and parabolic reflectors [14][15][16]. Unfortunately, the aforementioned approaches suffer from large sizes, design methodology, complex feeding network and fabrication processes, particularly in the high frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…But in these cases for achieving high gain, a large number of elements are needed, which not only increases the size of the antenna but also decreases its efficiency (Lafond et al, 2001), (Kärnfelt et al, 2006) & ( Soon-soo oh et al, 2004. It has been reported that for high gain, a superstrate layer can be added at a particular height of 0.5 0 above the ground plane (Choi et al, 2003) , (Menudier et al, 2007) & (Meriah et al, 2008).…”
Section: Fig 1 Short Range Communicationmentioning
confidence: 99%